2017
DOI: 10.1097/md.0000000000007634
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of costimulatory molecules CD40/CD40L and CD134/CD134L in coronary heart disease

Abstract: The aim of the study was to evaluate the potential role of CD40/CD40 ligand (CD40L) and CD134/CD134 ligand (CD134L) in the development of coronary heart disease (CHD) via the performance of a case-control study.The research objects were 234 cases of CHD patients and 120 cases of well-matched normal controls. Following the separation of peripheral blood mononuclear cells (PBMCs), real-time quantitative PCR (qRT-PCR), Western blot, immunohistochemistry, and flow cytometry were applied for the detection of mRNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The possible mechanisms by which the CD40 and CD40L systems affected atherosclerosis might be correlated with the immune inflammatory reaction (Gocmen et al, 2011;Fu et al, 2013;Hashem et al, 2014). Consistent with the results of the study by Chen et al (2017), we also found that both CD40 mRNA and protein expression levels were increased in the patients with luminal stenosis of ≥50% in ≥1 major vessel compared with the control group, though the level of CD40 was downregulated through bioinformatics analysis. The current discrepancy may result from the following possibilities.…”
Section: Discussionsupporting
confidence: 89%
“…The possible mechanisms by which the CD40 and CD40L systems affected atherosclerosis might be correlated with the immune inflammatory reaction (Gocmen et al, 2011;Fu et al, 2013;Hashem et al, 2014). Consistent with the results of the study by Chen et al (2017), we also found that both CD40 mRNA and protein expression levels were increased in the patients with luminal stenosis of ≥50% in ≥1 major vessel compared with the control group, though the level of CD40 was downregulated through bioinformatics analysis. The current discrepancy may result from the following possibilities.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, global OX40L overexpression and deletion increases and reduces fatty streak formation, respectively, in high‐fat diet‐fed mice 145,146 . Plaque‐resident CD4 + T cells and Mϕs express OX40 and OX40L, respectively, 145 and accumulation of TNFRSF4 and TNFSF4 transcripts, which encode OX40 and OX40L, correlate with CVD risk 159 . While there have been no clinical trials on these targets to date, an anti‐OX40 antagonistic Ab that elicits increased OX40 + T cells is currently under trial for individuals with solid tumors 160 …”
Section: Introductionmentioning
confidence: 99%
“…Other studies analyzed CD40 / CD40L mRNA expression levels in coronary artery disease (CHD), following the separation of peripheral blood mononuclear cells and qRT-PCR, and found significantly increased expression levels of both genes in the CHD group compared to the control group [24].…”
Section: Discussionmentioning
confidence: 99%